The Understanding of the Meaning of Intercultural Communication by Non-philological and Philological Students of Business English Courses at the University of Presov - Lucia Dančišinová (Acta Paedagogica Vilnensia)
Intercultural communication has been a widely discussed concept within the study of culture and communication in a social context. In classrooms today, intercultural communication is presented and explained even with greater variety than it is approached in theory and research. The aim of the paper is to analyse and compare the process of definition of intercultural communication in university textbooks with the definitions by philological and non-philological students of Business English courses at the University of Presov, to illustrate the possible problems with understanding the meaning as a result of different purposes and contexts of educational reality. The comparative analysis of definitions of intercultural communication by philological and non-philological students of Business English courses showed that philological students defined the concept in a more complex way, revealing a more developed linguistic competence in accordance with the definitions of intercultural communication in the analysed university textbooks. The analysis of university textbooks’ definitions also highlighted that approaches to intercultural communication are connected with disciplinary practices.